Influence of the biologically active dietary supplement Floravit® on the skin and hair structure in sable (Martes zibellina) - N. N. Loenko; I. E. Chernova; T. S. Kunitsina (Вавиловский журнал генетики и селекции)
It is important to search for new highly effective multicomponent compounds that are able to influence several of animals’ homeostasis systems simultaneously to improve the physiological adaptation of fur animals to different conditions of nutrition. This is the function of the feed additive Floravit® – a natural bioregulator. The compound is a combination of biologically active ingredients produced by the mycelial fungus Fusarium sambucinum. Studied was the effect of Floravit® on the structure of the skin and hair in adult female sable (Martes zibellina). The scientific and economic experiment was conducted at the JSC “Plemzavod Pushkinskyi” in the Moscow Region during the period of winter fur formation in October-November. The study of the morphological structure of the hair and skin cover was carried out in the chine, side and rump topographical areas. The structure of the guard hairs in the main topographical areas was examined on a scanning electron microscope. The experiment showed that administration of Floravit® per os to adult female sable at a dose of 1.0 ml per head per day throughout the period of winter pelt formation in October-November has an influence on the morphological structure of all the categories of hair on all topographic pelt areas. Animals in the test group exposed to Floravit® exhibited an increase in guide hair length on the chine and side, when compared to controls, by 4.1 mm (p < 0.001) and by 2.8 mm (p < 0.01), respectively. The length of guard hair on the chine, side and rump increased by 8.1, 7.8 and 7.8 mm (p < 0.001), respectively. An increase in down hair length was recorded in all areas of the pelt, when compared to controls, by 13.0, 4.5 and 6.3 mm (p < 0.001). An increase in dermal thickness was recorded in the chine area by 0.7 mm (p < 0.001). The specified changed in the skin and hair structure in sable adult females after using Floravit® have shown a positive influence on the quality of hair cover. As a result, bioregulator Floravit® takes part in the adaptation process of the sable organism to external factors.